Microearthquakes preceding a M4.2 Earthquake Offshore Istanbul. Issue 1 (December 2018) - Malin, Peter; Bohnhoff, Marco; Blümle, Felix; Dresen, Georg; Martínez-Garzón, Patricia; Nurlu, Murat; Ceken, Ulubey; Kadirioglu, Filiz; Kartal, Recai; Kilic, Tugbay; Yanik, Kenan
Abstract A primary hurdle in observing small foreshocks is the detection-limit of most seismic networks, which is typically about magnitude M1-1.5. We show that a start-up test of a borehole-based seismic network with a much lower detection limit overcame this problem for an Mw 4.2 earthquake. This earthquake occurred offshore of Istanbul, Turkey, on a fault system that is likely to rupture in an M > 7 event in the coming decades. In the three days before and two after, a total of 62 or more earthquakes, including at least 18 foreshocks, came from the mainshock source area. The signal similarity of the foreshocks shows a clear increase during the hours before the Mw 4.2 mainshock. Similar foreshock sequences have recently been reported for a few well monitored M > 7 plate-boundary earthquakes. The sequence surrounding the Mw 4.2 gives the impression of stochastic failures that ended up interactively unloading stress concentrations. The Mw 4.2 mainshock then resulted from the accumulated release of significantly smaller events, as suggested by other field and laboratory studies.